Approaches to Part of speech Tagging in Hindi Language: A Review - Vikash Yadav, Akanksha Sharma (International Journal of Advanced Science and Technology, 2020)
In the growing world of digital data, we deal with information search, retrieval and data translation on day to day basis. The part of speech tagging process plays a crucial role in this process. For the matter of fact as we come across more and more of Hindi documents on web currently, our aim for this paper is to discuss various tagging process available along with the performance of each in detail. Tagging here shall play a major role as with rich a language, Hindi is ambiguity is encountered more often. Here we will throw some light om the approaches available for POS tagging and the efficiency provided by some of these approaches mentioned.